Reducing the burden of Anemia: A cost effective sensitive method assessed among women attending post-partum clinic in an urban health centre - Gupta, Debjani Sen; Tapadar, Debajyoti (Asian Journal of Medical Sciences, 2021)
Background: Detection and early intervention of anemia in vulnerable population is of paramount importance in public health. Due to higher prevalence of anemia in women especially those who have just delivered and are breast feeding, this study would be of importance. Aims and Objective: This study was conducted in this population to find out the validity of clinical examination as an effective screening tool. Materials and Methods: Screening for anemia was conducted in study population by two members of health care providers (doctor and health worker). Results were compared with a gold standard. Standard guidelines were used to classify anemia as mild moderate and severe based on hemoglobin levels. Three sites were clinically examined for anemia and depending on pallor were graded as no, some, or severe pallor. Site wise sensitivity and specificity were considered. Result: Sensitivity of detecting anemia by clinical examination was 84.3 % by health worker and 64% by doctor. The specificity was 42.8% by health worker and 81.2% by doctor (inter observer agreement was 0.31 or fair). Diagnosing anemia by pallor in lower palpebral conjunctiva had a sensitivity of 66% for both some and severe anemia while that of palmer surface for severe anemia was 33% and moderate anemia was only 23%. On examining oral mucosa for the same purpose severe anemia had a sensitivity of 33% whereas moderate anemia yielded 66% and combination of all the three sites as described earlier had a sensitivity of 64%. Conclusion: The method of clinical examination as a screening tool for detecting anemia at field level holds good. However, examination of two or more sites should be advocated.